Magnetic Resonance Imaging and Spectroscopy Methods for Studying Obesity: Applications for Bariatric Surgery - Spicer, Abi (2025)
The prevalence of obesity in the population is increasing globally, leading to a rise in metabolic disorders such as Type-II Diabetes (T2D). Magnetic Resonance Imaging (MRI) and Spectroscopy (MRS) provide safe non-invasive techniques for investigating the physiology and metabolism of the human body. Whilst multinuclear MRS allows metabolic pathways that cannot be measured using 1H methods to be probed, in this thesis 13C and 31P MRS are used to study liver metabolism.